2017
DOI: 10.1111/anu.12522
|View full text |Cite
|
Sign up to set email alerts
|

Nigella sativa seed protects against 4-nonylphenol-induced haematotoxicity in Clarias gariepinus (Burchell, 1822): Oxidant/antioxidant rebalance

Abstract: 4-Nonylphenol (NP) is an emerging concern contaminant which is widely spread in the aquatic ecosystem. Nigella sativa seed (NSS) has multifaceted therapeutic values. This study aimed to give insight into the potential protective effect of NSS on NP-induced haematotoxicity in Clarias gariepinus through evaluation of haematological parameters, oxidant/antioxidant balance of blood lysate and histopathological investigation of blood smear. One hundred and fifty fish were divided into five groups (30/group). First … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 53 publications
3
7
0
Order By: Relevance
“…The content of black cumin seeds, thymoquinone, is proven laboratorically as immunomodulation because it can increase cellular and humoral immune response. Ethanol extract of black cumin seeds can increase the activity of phagocytosis and microbicidal macrophages [15][16][17]. Black cumin seed oil (BCSO) is thought to increase helper T cell function and affect T regulator, but until now there has been no research on the effect of BCSO on the number and activity of Th and Treg lymphocytes in DMBA-induced Sprague-Dawley (SD) rats.…”
Section: Introductionmentioning
confidence: 99%
“…The content of black cumin seeds, thymoquinone, is proven laboratorically as immunomodulation because it can increase cellular and humoral immune response. Ethanol extract of black cumin seeds can increase the activity of phagocytosis and microbicidal macrophages [15][16][17]. Black cumin seed oil (BCSO) is thought to increase helper T cell function and affect T regulator, but until now there has been no research on the effect of BCSO on the number and activity of Th and Treg lymphocytes in DMBA-induced Sprague-Dawley (SD) rats.…”
Section: Introductionmentioning
confidence: 99%
“…The 4-NP is toxic at concentrations of 17–3,000 μg/L, depending on the species of fish ( Mekkawy et al, 2011 ; Abou Khalil et al, 2017 ; Kotb et al, 2018 ; Sayed et al, 2019a ). A dose-dependent damage caused by 4-NP was evident in the current study, with similar results having been reported in other works as well ( Mekkawy et al, 2011 ; Al-Sharif, 2012 ; Sharma and Chadha, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different blood cell indices, including hemotoxicity and biochemistry, are used as major biomarkers of systemic responses to environmental stress in fish ( Mekkawy et al, 2011 ; Abou Khalil et al, 2017 ; Sayed and Soliman, 2018 ). In addition to apoptosis, micronucle and nuclear abnormalities, fish erythrocyte deformations have also been considered in toxicological studies on pollution-stress responses ( Talapatra and Banerjee, 2007 ; Mekkawy et al, 2011 ; Sayed et al, 2016a , 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…The swelled blood cells were recorded as common alteration which may be due to necrosis of their cellular outlines (Bushra et al, 2002). Abou Khalil et al (2017) reported erythrocyte alteration and micronuclei formation due to 4-Nonylphenol exposure. Erythrocytes are essential component for oxygen transport (Kuhn et al, 2017) and their deformation leads to respiratory dysfunction.…”
Section: Estimation Of Anti-oxidative Parametersmentioning
confidence: 99%